Conduct and Performance of Catfish Marketing Channels in the Special Region of Yogyakarta, Indonesia - Tenny Sylvia; Dyah Ismoyowati (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2020)
Catfish is one of the leading fishery commodities in Indonesia. Its production is high in the Special Region of Yogyakarta, that is, 45.44% of the total aquaculture production and 35.58% of the total aquaculture production. This study aimed to determine the type of marketing channels, including the conduct and performance of catfish marketing, and the efficiency of catfish marketing in the Special Region of Yogyakarta. Samples were obtained through purposive and snowball sampling, and data were collected through in-depth interviews with 30 respondents and examined through descriptive analysis and an SCP approach focusing on conduct and performance analysis. Result showed that two marketing channels were available. The first type consisted of fish farmers, collectors, and retailers, and the second type included fish farmers and retailers. Market conduct analysis revealed that the determination of the catfish price was dominated by collectors, marketing costs varied among players, and the government did not intervene with its trade. Market performance analysis indicated that fish farmers received 71.98% of their share on marketing channel 1 and 80.49% on marketing channel 2. The profit-to-cost ratios of collectors and retailers were 1.31 and 0.29 in marketing channel 1, respectively. In marketing channel 2, the profitto-cost ratio of retailers was 1.65. Therefore, marketing channel 2 was more efficient than marketing channel 1.